PELATIHAN DESAIN GRAFIS MENGGUNAKAN ADOBE PHOTOSHOP BAGI SISWA SMP NEGERI 1 JANGKAR - Siti Farhatus Shofiyyah; Zaehol Fatah (CV. Denasya Smart Publisher, 2026)
The development of digital technology requires students to possess adequate digital literacy and creativity skills. This study aims to describe the implementation of graphic design training using Adobe Photoshop, analyze the improvement of students’ digital skills and creativity, and identify students’ responses to the program. The research employed a descriptive approach involving 32 students of SMP Negeri 1 Jangkar. Data were collected through observation, questionnaires, documentation, and performance assessment. The results showed that student attendance reached 95%, active participation was 88%, and task completion was 84%. The average score increased from 58 in the pre-test to 84 in the post-test, with a mastery level of 84%. Most students responded positively to the training. The findings indicate that practice-based training using Adobe Photoshop is effective in improving students’ graphic design skills, creativity, and digital literacy.